The Place and Importance of Steam Educational Technology in Preschool Education - Ashurova Zarina Muxiddinovna (Zien Journals, 2022)
the article discusses the content and essence of the use of steam education technology in modern education, its specific features, advantages and opportunities
Keywords: STEAM; STEAM educational technology; abilities; competencies